2023
DOI: 10.3390/f14112168
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Basic Density of Woods Produced in the Brazilian Semiarid Region Subjected to Different Irrigation Regimes

Márcia Ellen Chagas dos Santos,
Rafael Rodolfo de Melo,
Diva Correia
et al.

Abstract: The present work aimed to evaluate the wood of fourteen genetic materials (nine species, between native and exotic, and five clones of Eucalyptus) cultivated under two post-planting irrigation regimes in the Brazilian semiarid region. For each genotype, six trees (11 years old) were selected and subjected to two initial irrigation regimes (up to 12 months and up to 36 months) after planting. Discs of different stem heights were taken: 0% (base), breast height (DBH), 20%, 40%, 60%, 80%, and 100%. Samples were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The density reduces from the base to the top in studied trees for axial and radial directions. This is a general trend since wood density is usually higher at the base due to the higher compaction of the stump tissues exerted by overlapping cells along the trunk and tree crown [12][13][14]20]. AYARKWA [21] and NIEMZ and SONDEREGGER [22] emphasized that the samples extracted from the top part of the tree have lower density and strength properties in most tree species.…”
Section: Physical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The density reduces from the base to the top in studied trees for axial and radial directions. This is a general trend since wood density is usually higher at the base due to the higher compaction of the stump tissues exerted by overlapping cells along the trunk and tree crown [12][13][14]20]. AYARKWA [21] and NIEMZ and SONDEREGGER [22] emphasized that the samples extracted from the top part of the tree have lower density and strength properties in most tree species.…”
Section: Physical Propertiesmentioning
confidence: 98%
“…Density is relevant for applying wood in different industrial sectors [12][13][14]. Analyzing the density variation in the axial and radial direction of the species A. colubrina, C. glandulosa, H. courbaril, and H. impetiginosus native to the Brazilian semi-arid region, SANTOS et al [12] found that in the radial direction, all species presented low-density values in the pith region, regardless of the height at which the samples were taken. This behavior was also observed for coniferous wood in studies by MELO [13] and ZAQUE et al [14], with the highest values found in the trunk's peripheral area.…”
Section: Introductionmentioning
confidence: 99%